Development and validation of a comprehensive health literacy tool for adults in Hong Kong - Tian, Cindy Yue; Mo, Phoenix Kit-Han; Dong, Dong; Cheung, Annie Wai-ling; Wong, Eliza Lai-Yi (Frontiers in Public Health, 2023)
Introduction: Health literacy (HL) refers to an individual’s ability to process and use health information to make health-related decisions. However, previous HL scales did not fully cover all aspects of this concept. This study aimed to develop a comprehensive HL scale (HLS-HK) and evaluate its psychometric properties among Hong Kong Chinese adults. Methods: A scale of 31-item covering Nutbeam’s framework, namely functional and interactive HL (FHL and IHL), and critical HL (CHL) within three subdomains: critical appraisal of information, understanding of social determinants of health, and actions to address social determinants of health, was developed based on previous literature review and Delphi survey. Cognitive interviews were performed to examine all items’ face validity in terms of three aspects: comprehensiveness, clarity, and acceptability. A cross-sectional survey was conducted to investigate the scale’s psychometric properties, including its internal consistency reliability, factorial structure validity, convergent validity, and predictive validity. Results: Nine interviewees participated in the cognitive interviews in October 2021. Based on the input from respondents, two items were deleted, two items were combined, and several items’ wording was revised. The other items were clear and readable. Finally, 28 items remained. A total of 433 adults completed the questionnaire survey between December 2021 and February 2022. After excluding one item with low inter-item correlations, the scale’s internal consistency reliability was acceptable, with a Cronbach’s alpha of 0.89. Exploratory factor analysis produced a five-factor model, as shown in the original theoretical framework. These factors accounted for 53% of the total variance. Confirmatory factor analysis confirmed that the fit indices for this model were acceptable (comparative fit index = 0.91, root mean square error of approximation = 0.06, and root mean square residual = 0.06). The scale is also significantly correlated with theoretically selected variables, including education and self-rated health. Conclusion: The HLS-HK is a valid and reliable tool for evaluating HL. Compared with existing tools, this scale extended the operationalization of FHL, IHL, and CHL and fully operationalized the CHL via three subdomains. It can be used to understand the difficulties and barriers that people may encounter when they use health-related information and services.